Essential conditions for the implementation of comprehensive school health to achieve changes in school culture and improvements in health behaviours of students. (December 2016) - Storey, Kate; Montemurro, Genevieve; Flynn, Jenn; Schwartz, Marg; Wright, Erin; Osler, Jill; Veugelers, Paul; Roberts, Erica
Abstract Background Comprehensive School Health (CSH) is an internationally recognized framework that holistically addresses school health by transforming the school culture. It has been shown to be effective in enhancing health behaviours among students while also improving educational outcomes. Despite this effectiveness, there is a need to focus on how CSH is implemented. Previous studies have attempted to uncover the conditions necessary for successful operationalization, but none have described them in relation to a proven best practice model of implementation that has demonstrated positive changes to school culture and improvements in health behaviours. Methods The purpose of this research was to identify the essential conditions of CSH implementation utilizing secondary analysis of qualitative interview data, incorporating a multitude of stakeholder perspectives. This included inductive content analysis of teacher (n  = 45), principal (n  = 46), and school health facilitator (n  = 34) viewpoints, all of whom were employed within successful CSH project schools in Alberta, Canada between 2008 and 2013. Results Many themes were identified, here called conditions, that were divided into two categories: 'core conditions' (students as change agents, school-specific autonomy, demonstrated administrative leadership, dedicated champion to engage school staff, community support, evidence, professional development) and 'contextual conditions' (time, funding and project supports, readiness and prior community connectivity). Core conditions were defined as those conditions necessary for CSH to be successfully implemented, whereas contextual conditions had a great degree of influence on the ability for the core conditions to be obtained. Together, and in consideration of already established 'process conditions' developed by APPLE Schools (assess, vision, prioritize; develop and implement an action plan; monitor, evaluate, celebrate), these represent the essential conditions of successful CSH implementation. Conclusions Overall, the present research contributes to the evidence-base of CSH implementation, ultimately helping to shape its optimization by providing school communities with a set of understandable essential conditions for CSH implementation. Such research is important as it helps to support and bolster the CSH framework that has been shown to improve the education, health, and well-being of school-aged children.